Socio-Cultural Implication in the Development of Educational Institutions of Kazakhstan: Interdisciplinary Research - Puzikova, Svetlana M.; Kudro, Nataliya M.; Assylov, Nurgali Z.; Moldasan, Kuanysh S.; Biryuk, Larisa A. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The purpose of the paper is to determine the specifics of the modern process of democratisation of the educational environment in Kazakhstan through the analysis of the implicative development of subject-to-subject interactions in educational institutions of the country. Background: The implication of traditionalism, patriarchy (collectivism), and individualism in the modern culture of Kazakhstani society form the basis for the development of a special, paternalistic type of subject-to-subject interactions in educational institutions of Kazakhstan. The specific nature of this type of interaction is in the preservation of students' value-and-role views about teacher’s functions in the educational process. Method: The study used a comparative method, conducted a questionnaire survey among students and schoolchildren with special educational needs, an expert survey of teachers, as well as in-depth interviews of schoolchildren and teachers at the second stage. Results: Based on the results of empirical studies, proposals are being developed on the conceptualisation of the development of the educational environment in the Kazakh school and on the further development of subject-to-subject relations in higher educational institutions. Democratisation of the educational process as a world trend necessitates considering local specific peculiarities when modernising the educational process in societies with a predominance of collectivist values. Conclusion: The authors, analysing the results of studies on the formation of an individual's subjectivity in various types of societies, having identified implicative relationships in the socio-cultural development of Kazakhstan, conclude that a new institutional significance of education is necessary as a fundamental factor in the overtaking modernisation of Kazakhstan.